Micro-Enterprise Development Strategy in Malinau District (Case Study of Micro-Enterprise in the Agricultural Sector in Malinau District, Kota) - Cerianita Dwi Yanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in regional economic development and in reducing unemployment. However, in 2017, the number of MSMEs in Malinau Regency decreased from 1,803 to 1,010 MSMEs, unlike other regions which saw growth. This decline was caused by limited capital and insufficient use of technology. This study aims to analyze the characteristics of MSMEs in Malinau Kota Subdistrict and to formulate strategies for their development. Using purposive sampling, this research involved 10 micro-enterprises in Malinau Kota Subdistrict, with data analysis employing descriptive qualitative, quantitative, and SWOT analysis. The results showed that micro-enterprises in the agricultural sector in Malinau Kota had business ages ranging from 1 to 16 years, employed 1-2 workers (mostly family members), and many had attended training. The types of businesses operated included various processed food products. The capital for these businesses mainly came from personal funds. The development strategy for MSMEs in Malinau Kota Subdistrict was categorized in quadrant I (SO strategy), which involves increasing production and product verification to meet market demand. The recommendations are that micro-business owners implement the SO strategy to increase production and utilize available labor, and that the government provide flexible credit assistance to support MSME capital.